New directions in international advertising research - Taylor, Charles R., 1961- (JAI, 2002)
This book addresses the need to move international advertising in new directions by summarizing existing knowledge in several areas, reporting findings of new studies, and providing future research directions. It is aimed both at scholars who have an interest in international advertising research as well as international advertising practitioners.
Keywords: Advertising -- Research.; Advertising -- Cross-cultural studies.; Marketing research.; elektronické knihy; electronic books